2002
DOI: 10.2741/chegini
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal molecular environment, adhesion formation and clinical implication

Abstract: Whether induced by infection, inflammation, ischemia, and/or surgical injury, peritoneal adhesions are the leading cause of pelvic pain, bowel obstruction and infertility. It is clear that while postsurgical peritoneal wounds heal without adhesions in some patients, others develop severe scarring from seemingly equal procedures; in addition, in the same patient, adhesions can develop at one surgical site and not in another. The mechanisms underlying the predisposition to form adhesions as well as their site sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
96
0
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 146 publications
2
96
0
7
Order By: Relevance
“…The onset of cellular and tissue injury is associated with remarkably regulated biochemical and morphological reactions that are mediated by both humeral and cellular immune systems [3]. Postoperative peritoneal adhesion formation appears to be caused by a complex local and systemic inflammatory response to tissue injury, ischemia, infection, or inflammation that results in an imbalance between fibrin formation and degradation [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The onset of cellular and tissue injury is associated with remarkably regulated biochemical and morphological reactions that are mediated by both humeral and cellular immune systems [3]. Postoperative peritoneal adhesion formation appears to be caused by a complex local and systemic inflammatory response to tissue injury, ischemia, infection, or inflammation that results in an imbalance between fibrin formation and degradation [16].…”
Section: Discussionmentioning
confidence: 99%
“…Using a surgically-induced cecal abrasion model in mice, Chung et al [17] demonstrated that Th1 CD4 ϩ ␣␤ cells are critical in the development of peritoneal adhesions and that these activated T cells become the predominant cells in the peritoneal cavity shortly after tissue injury and throughout adhesiogenesis. Several chymokines and cytokines, including interleukin, M-CSF, GM-CSF, and MCP-1, regulate the fibrinolytic process [3]. TGF-␤ has been correlated with excessive extracellular matrix modifications by induction of several proteins such as collagenase activity, fibronectin, and by inhibition of matrix degradation [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to endometriosis, adhesions appear to be the main cause of morbidity after surgical trauma, peritonitis, pelvic inflammatory disease, and other related disorders. It has become accepted that the development of pelvic adhesions involves inflammatory responses, abrogated fibrinolysis, and the protease/protease inhibitor system, as well as angiogenesis (10)(11)(12)(13). Inflammatory responses that may lead to induction of adhesion formation may primarily depend on the production of proinflammatory cytokines interleukin-1 (IL-1), IL-6, and tumor necrosis factor (TNF) (10,14,15).…”
mentioning
confidence: 99%
“…Most studies have focused on revealing of the mechanism of postsurgical adhesion formation (10)(11)(12)(13), and still little is known about the putative mechanism(s) of their formation in the course of endometriosis. It is plausible that pelvic adhesion formation in patients with endometriosis depends in part on local inflammatory reactions and abrogated angiogenic activity.…”
mentioning
confidence: 99%